2003
DOI: 10.1124/jpet.103.050583
|View full text |Cite
|
Sign up to set email alerts
|

A Lymphocyte-Generated Fragment of Vasoactive Intestinal Peptide with VPAC1 Agonist Activity and VPAC2 Antagonist Effects

Abstract: Vasoactive intestinal peptide receptors 1 (VPAC1) and 2 (VPAC2) have been identified in humans. Cell lines expressing only VPAC1 (HT-29) or VPAC2 (Molt-4b) were identified using real-time reverse transcriptase polymerase chain reaction. Vasoactive intestinal peptide (VIP) and related peptides, VIP Ϫ6 -28 , VIP , previously isolated from cultures of human leukocytes, were evaluated for their ability to bind to VPAC1 and VPAC2 and to increase the levels of cAMP in HT-29 and Molt-4b cells. VIP bound to membranes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(12 citation statements)
references
References 35 publications
0
12
0
Order By: Relevance
“…Interestingly, human leukocytes were found to produce several VIP fragments, including VIP10-28, but their roles were completely unknown. 34 Our data could give now a physiological significance to the production of these fragments. Most of these neuropeptides appear very early in the evolution and their sequences are well conserved, suggesting that they must play an ancient role, probably as important components of host innate defense.…”
Section: Neuropeptides As Endogenous Trypanolytic Factors M Delgado Ementioning
confidence: 67%
“…Interestingly, human leukocytes were found to produce several VIP fragments, including VIP10-28, but their roles were completely unknown. 34 Our data could give now a physiological significance to the production of these fragments. Most of these neuropeptides appear very early in the evolution and their sequences are well conserved, suggesting that they must play an ancient role, probably as important components of host innate defense.…”
Section: Neuropeptides As Endogenous Trypanolytic Factors M Delgado Ementioning
confidence: 67%
“…Cell membranes were isolated as previously described. 28 Briefly, 100-mg ileal tissue from 4-week-old littermates was used. Sections were opened longitudinally, rinsed with saline, and epithelial cells were removed with gentle scraping directly into buffer A (20-mmol/L 4-(2-hydroxethyl)-1-piperazinethanesulforic acid, pH 7.4, 5-mmol/L EDTA, 2-mmol/L MgCl 2 , 1-mmol/L A-mercaptoethanol, 150-mmol/L sodium chloride, and 50-Kg/mL phenylmethylsulfonylfluoride).…”
Section: Membrane Isolation From Ileum and Competitive Vip Bindingmentioning
confidence: 99%
“…Vasoactive intestinal peptide binds with nearly equal affinity to VPAC1 and VPAC2; however, the potency of VIP for activation of adenylate cyclase and cAMP generation is much higher when interacting with VPAC1 than with VPAC2. 28 Vasoactive intestinal peptide is capable of binding to PAC1, albeit with much lower affinity than PACAP, which is its preferred ligand. 29 Mice lacking VIP seem to have a mild phenotype, perhaps because PACAP can induce signal transduction via PAC1, VPAC1, or VPAC2, suggesting that VIP and PACAP can each function as a ''spare ligand'' when the other is deficient.…”
mentioning
confidence: 99%
“…A potent general VPAC 1 receptor antagonist is the chimeric VIP/GRF derivative, PG 97-269 (Gourlet et al, 1997c), whereas no generally used VPAC 2 receptor antagonists have been developed. Recently, the endogenous VIP fragment generated at the surface of lymphocytes by protease activity (Goetzl et al, 1989b), VIP 4 -28 , has been shown in vitro to be a potent agonist for VPAC 1 and a potent antagonist for VPAC 2 (Summers et al, 2003). The role of this VPAC 2 endogenous antagonist could be of physiological importance since fine modulation can be achieved in cells differentially expressing VPAC1 or VPAC2 receptors.…”
Section: B Biochemical Pharmacological and Signaling Key Features mentioning
confidence: 99%